The universe within [compact disc, unabridged] : [discovering the common history of rocks, planets, and people] - Shubin, Neil (Random House Audio Publishing Group ; Books on Tape, 2013)
Neil Shubin takes an even more expansive approach to the question of why we are the way we are. Starting once again with fossils, Shubin turns his gaze skyward. He shows how the entirety of the universe's 14-billion-year history can be seen in our bodies. From our very molecular composition (a result of stellar events at the origin of our solar system), he makes clear, through the working of our eyes, how the evolution of the cosmos has had profound effects on the development of human life on earth.